2021
DOI: 10.3390/ani11123465
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Identification and Characterization of a Genotype 3 Hepatitis E Virus (HEV) Strain Detected in a Wolf Faecal Sample, Italy

Abstract: Hepatitis E virus (HEV) infection is a major health problem worldwide. In developed countries, zoonotic transmission of HEV genotypes (Gt) 3 and 4 is caused by the ingestion of raw or undercooked meat of infected pigs and wild boars, the main reservoirs of HEV. However, additional animals may harbour HEV or HEV-related strains, including carnivores. In this study, we investigated the molecular epidemiology of orthohepeviruses in wild canids by screening a total of 136 archival faecal samples, collected from wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…This result agrees with previous studies, in which HEV RNA has never been found in dog serum [ 32 , 37 , 38 ], body cavity transudate [ 28 ], feces [ 37 ], or liver [ 13 ], even after experimental infection [ 32 ]. In a recent study, HEV RNA has been identified in a wolf ( Canis lupus italicus ) rectal swab, which could be due to the predation of an infected animal [ 39 ]. Following this evidence, the negative results from serum samples, and the result on sera samples even after experimental infection, we considered rectal swabs a suitable sample for our study.…”
Section: Discussionmentioning
confidence: 99%
“…This result agrees with previous studies, in which HEV RNA has never been found in dog serum [ 32 , 37 , 38 ], body cavity transudate [ 28 ], feces [ 37 ], or liver [ 13 ], even after experimental infection [ 32 ]. In a recent study, HEV RNA has been identified in a wolf ( Canis lupus italicus ) rectal swab, which could be due to the predation of an infected animal [ 39 ]. Following this evidence, the negative results from serum samples, and the result on sera samples even after experimental infection, we considered rectal swabs a suitable sample for our study.…”
Section: Discussionmentioning
confidence: 99%
“…Pigs and wild boars are usually considered “reservoirs”. Therefore, these animal species are fundamental for a better understanding of the spread of HEV, even though new animal hosts and viral strains are recently reported [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, even a small number of sequences available for analysis permit concluding with a high level of confidence, that HEV-3 and HEV-4 infection in deer is not always a spillover from suides, wild or domestic, it also may be a result of stable virus transmission in the deer population. No doubt, suides are the primary reservoir of HEV-3 and HEV-4 and may be a source of infection for a number of mammal species that have a dietary link to suides [ 20 ] or share a habitat [ 21 ]. Moreover, transmission patterns from our analysis confirm the observation that domestic pigs may serve as a source of HEV infection for wildlife [ 22 ].…”
Section: Resultsmentioning
confidence: 99%